Reclaiming constructivism: towards an interpretive reading of the ‘Social construction framework’ - Barbehön, Marlon (Policy sciences, 2020)
The ‘Social Construction Framework’ which addresses the relationship between policy design and the construction of target groups is one of the central approaches within the field of policy theories. Yet, despite its name, the approach builds on several naturalist premises, and its analytical components are informed by principles rooted in positivist methodologies. Against this background, this article conducts a thorough critique of the framework’s constructivist shortcomings, and it develops a strictly constructivist and interpretive reading of its core arguments. The analytical value is substantiated by presenting original empirical research on the meaning of the ‘middle class’ in German welfare policy. We will show that, firstly, group construction is not only a matter of positive or negative evaluation, but more fundamentally an act of boundary-drawing, with differently constructed middle classes enabling different welfare policies. Secondly, we will show that target group constructions are always entangled with the construction of the group’s outside, leading to the stabilisation and legitimisation of hierarchies between the middle class and ‘the others’ in society. Thirdly, we demonstrate that the power of a target group is also a matter of social construction, with the middle class obtaining its hegemonic position from an order of knowledge that equates the middle with ‘the normal’ and ‘the common good’. Based on these insights, the article raises a more general plea against the translation of constructivism into a middle-range theory of the policy process and instead emphasises the ontological and epistemological distinctiveness of strict constructivism and interpretive methodologies.
Gesehen am 01.09.2021